Gene Expression Pattern of Peyer’s Patch Lymphocytes Exposed to Kagocel Suggests Pattern-Recognition Receptors Mediate Its Action - Andreev-Andrievskiy, Alexander A.; Zinovkin, Roman A.; Mashkin, Mikhail A.; Frolova, Olga Yu.; Kazaishvili, Yuriy G.; Scherbakova, Victoria S.; Rudoy, Boris A.; Nesterenko, Vladimir G. (Frontiers in Pharmacology, 2021)
Kagocel is a synthetic carboxymethylcellulose derivative copolymerized with gossypol. Clinical data evidence its safety and efficiency for the treatment of flu and other viral infections via enhancement of interferon production. The gut-associated lymphoid tissue seems a likely site of kagocel action. The study was aimed to investigate the molecular mechanisms of its action using murine Peyer’s patches lymphocytes as a test system and the cytokines production and gene expression patterns as the primary outcomes. The Peyer’s patches lymphocytes isolated from BALB/c mice were stimulated with concanavalin A, or, to mimic viral infection, with a combination of concanavalin A and TLR3 ligand poly I:C. After 24h of stimulation the cells were treated with saline, 30, 100, or 300 µg/ml of kagocel, or, as positive controls, 300 µg/ml oats b-D-glucan or 300 µg/ml lentinan. After 24 and 72 h of incubation with these drugs cytokines production was analyzed with ELISA and gene expression pattern was investigated using nCounter Inflammation panel chips followed by bioinformatics analysis. Expression of genes involved in the inflammatory response, antiviral defense, lymphocytes survival and proliferation (C1qa, C2, C3, Ccl21a, Il11, Il1b, Il23a, Il5, Ltb4r2, Alox15, Pla2g4a, Ptger1, Mapkapk5, Hras, Ifna1, Tlr2, Mrc1, Mx2) was upregulated in kagocel-treated Peyer’s patches lymphocytes. A list of plausible transcription factors (CEBPs, IRF, NFkB, RXR, Stat, Tead4 and ZSCAN) and master-regulators has been identified (cIAP, CIKS, dock9, MEKK1, FXR, IKK, IRAK, TRAF, dsRNA:TLR3:TRIF). The changes in gene expression pattern and the outcomes of bioinformatics analysis suggest that pattern recognition receptors, TLRs and dectin-1, are key mediators of kagocel immunomodulatory action, with the possible involvement of interferon autocrine loop. The genes upregulated with kagocel include diverse components of the innate immune defense system.